THE EFFECT OF SERVICES AND IMAGES ON TOURIST SATISFACTION AS USERS OF TRANS-JAKARTA TO TOURISM DESTINATIONS AT RAGUNAN WILDLIFE PARK DURING THE COVID-19 PANDEMIC - Gagih Pradini; Rahayu Lestri; Resti Hardini (GoAcademica Research dan Publishing, 2021)
Tourism is one of the essential components to drive economic growth around the world in recent times, one of the tourism activities is visiting tourism destinations. This research activity is expected to provide the correct strategic input for Transjakarta companies during the pandemic. The variables used are Service Quality (X1) and Image (X2). Determining the location and channel used to provide services to customers involves thinking about how to deliver or deliver services to customers and where this will be done. Problem Solving Orientation states and Dependent Satisfaction (Y1) where service, product, and image benchmarks are maintained during the pandemic despite following health protocols.